Comportamento ingestivo de frangos de corte mediante diferentes condições térmicas - Bevilaqua, Bernardo (2016)
Heat stress directly affects the performance and feed intake, being reflected by animal behavior. The use of animals as biosensors through the behavior, it is more efficient than the monitoring of temperature and relative humidity, allowing you to capture intermediate stress conditions. The aim of this study was to evaluate the ingestive behavior of broiler chickens under three different temperature conditions through image analysis. The experiment was carried out in three climatic chambers being used 108 male chickens of Hubbard lineage. Behavioral observations were performed in poultry aged 21, 28, 35 and 42 days. For each age were housed 27 birds per nine ambient condition for 72 hours, wherein 48h for adaptation and 24 hours for observation of behaviors through pictures and capture further evaluation. In every age, the birds used were distinct and individually identified. All birds were from the same batch and received food and water ad libitum. We used three treatments (Comfort = recommendation temperature strain, Heat = 8 ° C above the comfort temperature and Cold = 8 ° C below the comfort temperature) with nine replicates, each bird was an experimental unit. We collected the feeding behavior parameters: time consumption, length of stay, number of daily visits and time to the feeder and water dispenser being submitted to the Pearson correlation test, analysis of variance F test at 5% significance. Performance data were collected amount of food and water consumed by each treatment every hour and weight gain. Behaviors for the times cooler area of occupation times, feeder and open area were affected by the thermal conditions with the birds respond differently according to age. The thermal conditions affect the number of visits per hour and time of visit by staying the equipment. There was a high correlation between time consumption and time spent on equipment and between length of stay and amount consumed feed and water. From the data of birds together regressions were generated to quantify intake and water intake of feed intensity and residence time through the different thermal conditions. The thermal conditions with a variation of plus or minus about 8 ° C Comfort did not affect the weight gain of the birds, however, adversely affected in the uniformity of the birds that were out of thermal comfort.